The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s003350020035
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of 64 genes expressed in 28-day-old pig embryo to radiation hybrid map

Abstract: A swine resource family was constructed at the National Institute of Animal Industry, Japan, in order to determine the genetic regions responsible for economically important traits, including fetus development. To identify genes expressed in the early stage of embryo development, we cataloged and mapped genes expressed in a 28-day-old normal pig embryo. In this effort, we have mapped 64 genes, which have map information in human genome onto a swine radiation hybrid (RH) map, IMpRH. These mappings provided addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…As shown in Supplementary Table 1 (www.karger.com/doi/ 10.1159/000087523), ITIH2 was mapped to SSC10, which was consistent with both the somatic-hybrid assignment and the genetic-linkage analysis (Ponsuksili et al, 2001;Nonneman and Rohrer, 2003), but inconsistent with the mapping results of Karnuah et al (2001). Therefore, to confirm the results of this study, the fragment amplified with the primer pair in the study of Karnuah et al (2001) was sequenced, revealing that the sequence of that fragment, though of the expected size, differed from the sequence used for the primer design.…”
Section: Assignment Of Genes To Swine Chromosomesmentioning
confidence: 57%
See 1 more Smart Citation
“…As shown in Supplementary Table 1 (www.karger.com/doi/ 10.1159/000087523), ITIH2 was mapped to SSC10, which was consistent with both the somatic-hybrid assignment and the genetic-linkage analysis (Ponsuksili et al, 2001;Nonneman and Rohrer, 2003), but inconsistent with the mapping results of Karnuah et al (2001). Therefore, to confirm the results of this study, the fragment amplified with the primer pair in the study of Karnuah et al (2001) was sequenced, revealing that the sequence of that fragment, though of the expected size, differed from the sequence used for the primer design.…”
Section: Assignment Of Genes To Swine Chromosomesmentioning
confidence: 57%
“…ITIH2 was shown to reside on SSC10 by somatic hybrid assignment and genetic-linkage analysis (Ponsuksili et al, 2001;Nonneman and Rohrer, 2003), whereas Karnuah et al (2001) mapped it on SSC3 using the IMpRH panel. Therefore, in order to investigate the discrepancy in its chromosomal position, a primer pair was redesigned for ITIH2 in the present study.…”
Section: Primer Designmentioning
confidence: 99%
“…When this observation is combined with the findings of Karnuah et al (2001), in which many breaks were found in the "conserved synteny" regions between human and swine chromosomes demonstrated by a recent extensive study (Pinton et al, 2000), it is predicted that synteny conservation between human and swine chromosomes would be much more fragmentary than that reported by Pinton et al (2000).…”
Section: Resultsmentioning
confidence: 77%
“…inra.fr/lgc/pig/compare/HSA.htm). As a result, a number of breaks in conservation of synteny between human and swine chromosomes have been demonstrated (Pinton et al, 2000;Karnuah et al, 2001), which could not be predicted from the correspondence revealed by ZOO-FISH (Goureau et al, 1996). In the present study, using 910 sequence-tagged sites (STSs) from human chromosome (HSA) 1p36 → p35 (35 Mbp) (Chen et al, 2001), we have attempted to construct a more detailed comparative map between this human chromosome and its corresponding swine chromosome (SSC) 6 region, which appears to harbor QTLs (Quantitative Trait Loci) for backfat thickness (Rohrer, 2000) and average daily gain (Bidanel et al, 2001).…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…Moreover mapping on the radiation hybrid panel IMpRH is in full swing (Hawken et al, 1999;Karnuah et al, 2001;Korwin-Kossakowska et al, 2002;Krause et al, 2002;Rink et al, 2002;Lahbib-Mansais et al, 2003) and 6000 markers are already mapped. A first generation RH comparative map of the porcine and human genome has already been published (Rink et al, 2002;Lahbib-Mansais et al, 2003) but this map includes only EST markers.…”
Section: Copyright © 2003 S Karger Ag Baselmentioning
confidence: 99%